Violencia de pareja, confianza interpersonal y esperanza: un estudio entre adultos portugueses - Minas, Bárbara (International journal of developmental and educational psychology, 2021)
According to results presented in several reports from the World Health Organization, violence in intimate relationships is a phenomenon whose incidence covers the most diverse populations on a universal scale. Allowing for recent information included on a report from a Portuguese association that gives support to victims (APAV, 2014), this is a very serious problem with severe consequences, including death. Being a complex problem, so interconnected with several variables that have an impact on developmental trajectories, there is an increased need for research and intervention. Objectives: Considering previous research on interpersonal trust, hope and intimate partner violence, this exploratory study aims to examine the relationship between intimate partner violence, interpersonal trust in the intimate partner and hope for the future. Also, prevalence of violence in intimate relationships will be addressed. Methods: In this cross-sectional study, the sample includes 302 subjects (202 women and 100 men), aged 18 to 63 years (M = 29, SD =10.78). Data collection was performed through a protocol that includes a Sociodemographic Questionnaire, the Portuguese adaptation of the Rotenberg s Specific Trust Scale-Adults, the Scale of Beliefs about Marital Violence, the Inventory of Marital Violence and the Scale of the Future. Results: A worrying prevalence of violence in intimate relationships was found, whether in present or in past relationships. Results also show the existence of weak, but statistically significant negative associations between interpersonal trust and violence, considering both victimization and perpetration. Although modest, some significant positive relationships between certain aspects of hope and interpersonal trust were found. In addition, results show some significant differences in legitimating beliefs of intimate partner violence by age, sex and socioeconomic status. Discussion: Interpretation of these findings, study limitations and suggestions for future investigations are presented and discussed.Según los resultados presentados en varios informes de la Organización Mundial de la Salud, la violencia en las relaciones íntimas es un fenómeno cuya incidencia abarca las más diversas poblaciones a escala universal. Teniendo en cuenta la información reciente incluida en un informe de una asociación portuguesa que da apoyo a las víctimas (APAV, 2014), se trata de un problema muy grave con consecuencias severas, incluyendo la muerte. Al tratarse de un problema complejo, tan interconectado con diversas variables que inciden en las trayectorias de desarrollo, hay una mayor necesidad de investigación e intervención. Objetivos: Teniendo en cuenta las investigaciones previas sobre la confianza interpersonal, la esperanza y la violencia en la pareja, este estudio exploratorio pretende examinar la relación entre la violencia en la pareja, la confianza interpersonal en la pareja y la esperanza en el futuro. También se abordará la prevalencia de la violencia en las relaciones íntimas. Métodos: En este estudio transversal, la muestra incluye 302 sujetos (202 mujeres y 100 hombres), con edades comprendidas entre los 18 y los 63 años (M = 29, SD =10,78). La recogida de datos se realizó mediante un protocolo que incluye un Cuestionario Sociodemográfico, la adaptación portuguesa de la Escala de Confianza Específica de Rotenberg-Adultos, la Escala de Creencias sobre la Violencia Marital, el Inventario de Violencia Marital y la Escala de Futuro. Resultados: Se encontró una preocupante prevalencia de violencia en las relaciones íntimas, tanto en las relaciones actuales como en las pasadas. Los resultados también muestran la existencia de asociaciones negativas débiles, pero estadísticamente significativas, entre la confianza interpersonal y la violencia, considerando tanto la victimización como la perpetración. Aunque modestas, se encontraron algunas relaciones positivas significativas entre ciertos aspectos de la esperanza y la confianza interpersonal. Además, los resultados muestran algunas diferencias significativas en las creencias legitimadoras de la violencia de pareja según la edad, el sexo y el nivel socioeconómico. Discusión: Se presenta y discute la interpretación de estos resultados, las limitaciones del estudio y las sugerencias para futuras investigaciones